The impact of inter-provincial inequities in higher education on the legal protection of personality rights in China - Qiong Wu; Othman Talib; Mohamad Termizi Borhan (Cogent Education, 2025)
The personality right, as an innate right, must be protected if society is to achieve sustainable development. The rights are increasingly emphasized today, and the impact of higher education on the legal protection of the right to personality in China is particularly far-reaching, given that China’s population is large and its educational resources are unevenly developed from province to province. This article discusses the important relevance of higher education to the legal protection of personality rights and the imbalance that exists in China’s higher education, which also affects the unbalanced development of the legal protection of personality rights between provinces. Through quantitative research, collecting data on Chinese people’s education, especially higher education, for more than 10 years, it shows urban areas have a significant advantage over rural areas, and males have a significant advantage over females. This situation also exists in personality rights cases (PRCs) and varies greatly from province to province, that confirms the unbalanced development of higher education in China has had a profound impact on the inter-provincial inequities of the legal protection of personality rights. It is particularly necessary to support the development of higher education by increasing special education funding and popularizing and promoting education on the legal protection of personality rights to realize the sustainable development of Chinese society in the current domestic and international environment.